Analisis Kestabilan Proses dan Penyebab Defect Menggumpal pada Spray drying Kopi Instan Menggunakan Statistical Process Control - Abby yazid bustommy; Sita Kurniaty Ratoko (Journal Information Technology Engineering and Science (JITES), 2026)
The food and beverage industry is required to produce products with consistent quality, particularly powder-based products that are highly sensitive to process variations. In instant coffee production, the spray drying process plays a critical role in determining the physical quality of the final product, where uncontrolled process parameters may lead to defects such as caking. This study aims to analyze the quality of the spray drying process and to evaluate process stability using a statistical process control (SPC) approach. A quantitative descriptive case study was conducted using production and defect data from January to June 2024. Time-series data were analyzed through defect rate calculation, Pareto analysis to identify dominant causes, cause–effect analysis using the 6M approach, and proportion control charts (p-charts). The results show that defect rates fluctuate across the observation periods, with caking identified as the dominant defect caused by unstable burner temperature, high concentrate brix values, and nozzle clogging. The p-chart analysis indicates that the spray drying process is statistically out of control, highlighting the need for continuous monitoring and control of critical process parameters to reduce variability and prevent recurring defects.